Development of National Education in General and Geographical Context in The Study of Philosophy of Education - Sejati, Andri Estining; Maulidian, Muhammad Okta Ridha; Handoyo, Budi (International Journal of Geography, Social, and Multicultural Education, 2025)
The development of national education in Indonesia is a dynamic process and continues to change in line with the times, the needs of society, and global demands. This paper aims to analyze the development of national education (general and geography) in the study of educational philosophy. The literature study methodology looks at national education policies and their relevance to various schools of educational philosophy. Literature data on the development of national education amounted to 28, and educational philosophy 18, collected from government regulatory documents, books, journal articles, and proceedings articles. The data was analyzed using qualitative descriptive. The development of Indonesian national education continues to adapt to the dynamics of the times through the Merdeka Belajar, deep learning, and Kampus Merdeka policies. Geography learning is in line with these policies. Integration of educational philosophy to create a holistic, relevant, and globally competitive education system. Philosofy such as idealism, realism, constructivism, progressivism, pragmatism, and essentialism provide a basis for thinking for the development of national education that is holistic, adaptive, and relevant to global dynamics. The Merdeka Belajar and other educational policies viewed philosophically can accommodate diversity, innovation, and local and global needs to realize national education goals.